Silicon Anodes with Improved Calendar Life Enabled By Multivalent Additives. Issue 37 (25th August 2021) - Zhang, Yunya; Li, Xiang; Sivonxay, Eric; Wen, Jianguo; Persson, Kristin A.; Vaughey, John T.; Key, Baris; Dogan, Fulya
Abstract: Silicon is widely recognized as the most promising upgrade for graphite anodes due to its much higher capacity, natural abundance, and ability to be directly applied in the slurry‐based, roll‐to‐roll production lines. However, in addition to the fast capacity decay, silicon anodes also suffer from inferior calendar life in practical applications due to the unstable solid‐electrode interface (SEI). Until now, strategies to effectively improve the calendar life by tailored SEIs remain largely unclear, especially in high‐Si content, zero‐graphite anodes. Here, silicon anodes with superior calendar life are developed by adding small concentrations of multivalent salts into the baseline electrolyte. The Ca additive reacts with the F ions in the electrolyte, forming a layer of nanocrystalline CaF2 that is closely coated around the silicon particles. The CaF2 ‐enabled new SEI is strong and dense, which effectively protects the silicon core from side reactions, leading to lower capacity decay after calendar aging at high voltage. More importantly, the Ca additive is effective universally for all available commercial silicon or SiO sources. This study provides a feasible and low‐cost solution for developing silicon anodes with long calendar life, paving the way towards commercially viable silicon anodes. Abstract : Silicon is widely recognized as the most promising upgrade for graphite anodes. However, silicon anodes suffer from inferior calendar life in practical applications due to the unstable solid‐electrode interface (SEI). Here, silicon anodes with superior calendar life are developed by adding a touch of Ca salts, which enables a robust SEI with CaF2 that protects Si core from side reactions.